Ocse Pisa 2012. Contributi di approfondimento - Palmerio, Laura (Varie - Open Access, 2017)
The Programme for International Student Assessment (PISA) is a triennial international survey which aims to evaluate education systems worldwide by testing the skills and knowledge of 15-year-old students. This volume contains a collection of contributions from multidisciplinary fields and working environment (school, university, research). The contributions have been selected through a call for papers and submitted to peer review by qualified experts.